Implementation of Group Guidance Using Spinner Media (Interactive Spinning Wheel) To Improve Students' Self-Esteem - Nasution, Siti Walidah (Universitas Negeri Medan, 2025)
The purpose of this study was to determine the effectiveness of implementing group guidance services using spinner media (interactive spinning wheel) in improving self-esteem of grade VIII students at SMP Negeri 5 Percut Sei Tuan. This study uses a qualitative research type by applying the guidance and counseling action research method (PTBK). This is because the research was conducted through a series of stages. This study was conducted in two cycles starting from identifying problems in the classroom, then designing and implementing intervention actions, conducting reflections, analyzing the results, and making improvements in the second cycle. The results showed an increase in students' self-esteem after participating in group guidance services with spinner media. In cycle I, students still seemed hesitant and not fully open in expressing their feelings. However, the spinner media began to open up space for expression although it was not evenly distributed. Entering cycle II, significant changes were seen: students were more enthusiastic, open in sharing experiences, and showed more reflective and honest interactions. This indicates that the use of spinner media is effective in creating a safe group atmosphere and supporting increased self-esteem. group guidance services using spinner media (interactive spinning wheel) have a positive impact on increasing students' self-esteem. These changes are evident in the attitudes, behavior, and ways in which students view and value themselves after actively participating in the service.